2022
DOI: 10.3389/fmicb.2022.813774
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxin-Associated Gene A-Negative Helicobacter pylori Promotes Gastric Mucosal CX3CR1+CD4+ Effector Memory T Cell Recruitment in Mice

Abstract: BackgroundHelicobacter pylori can cause many kinds of gastric disorders, ranging from gastritis to gastric cancer. Cytotoxin-associated gene A (CagA)+H. pylori is more likely to cause gastric histopathologic damage than CagA–H. pylori. However, the underlying mechanism needs to be further investigated.Materials and methodsMice were intragastrically administered equal amounts of CagA+ or CagA–H. pylori. Four weeks later, 24 chemokines in stomachs were measured using a mouse chemokine array, and the phenotypes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…While CX3CR1 can be involved in immune cell trafficking, this function of CX3CR1 on CD4 T cells is likely to be context specific. For example, one study found in a model of LCMV13 infection CX3CR1 to be dispensable for T cell trafficking to the spleen, lung, and liver, while others have found it necessary in models of Helicobacter pylori infection and allergic asthma (26,28,39). Our own analysis on two different models of helminth infection affecting two different tissues supports this view that CX3CR1 is involved in CD4 + T cell trafficking in some instances but not others.…”
Section: Discussionsupporting
confidence: 61%
“…While CX3CR1 can be involved in immune cell trafficking, this function of CX3CR1 on CD4 T cells is likely to be context specific. For example, one study found in a model of LCMV13 infection CX3CR1 to be dispensable for T cell trafficking to the spleen, lung, and liver, while others have found it necessary in models of Helicobacter pylori infection and allergic asthma (26,28,39). Our own analysis on two different models of helminth infection affecting two different tissues supports this view that CX3CR1 is involved in CD4 + T cell trafficking in some instances but not others.…”
Section: Discussionsupporting
confidence: 61%
“…Previously, Heqiang et al found that CagA- Helicobacter pylori infection induced the release of CX3CL1 from the gastric epithelium which subsequently recruited CD4 T memory cells. This recruitment reduced the infection and damage caused by H. pylori [ 33 ]. The CXCL14, which is named as B cell and monocyte-activated chemokine (BMAC) was associated with the deterioration and metastasis of multiple malignant tumors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that a population of BIRC5 + stem-cell-like proliferating cluster of myeloid cells is present in the liver during chronic infection with S. mansoni and could be a general feature of inflammation, not unique to atherosclerosis (3). However, there are also BIRC5 + lymphocytes, which may be derived from a small subset of T cells that can also express CX3CR1 (22,23).…”
Section: Resultsmentioning
confidence: 99%